Extraccion de pectina en dos estados de maduracion de achotillo (Nephelum lappceum) para la elaboracion de mermeladas. - Ochoa Bustamante, Mauricio Javier (2013)
This research was conducted in the laboratory of Basic Uses of Quevedo State Technical University located at km 1 ½ via Sto . Sunday, raising the following objectives : To determine physical parameters and achotillo Chemical in fruits ( Nephelium lappaceum ) in two stages of maturity ; Determine the performance of pectin from peel of achotillo ( Nephelium lappaceum ) in two stages of maturity ; Develop jam using pectin extracted achotillo rind ( Nephelium lappaceum ) and evaluate organoleptic parameters preferably in a jam. For the physical parameters green fruits were harvested 400 and 400 ripe fruits of the town of Canton Good Faith farm " Cevallos " the process of extracting pectin peel Achotillo ……